(untitled) (Research, Society and Development, 2021)
Bacterial resistance to antibiotics has become a serious public health problem worldwide, affecting thousands of people. Thus, there is a need to seek alternative ways to combat them. Therefore, this research aimed to verify the antimicrobial effect of the extract of Annona muricata L. against ATCC strains of Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Staphylococcus aureus. The material was collected and the extracts were obtained, then the bacterial strains were prepared for susceptibility testing. The tests proceeded in three stages: crude extracts, chemically fractionated extracts and tests with serial dilutions. Soursop antibacterial activity was observed against all strains tested, the most significant result being the crude extract of the fruit against the strain of E. coli with a halo equal to 22mm. In relation to the tests with the extracts already purified, the fractions from the fruit have more relevant action. The Hexane fraction corresponded to the most expressive results, obtaining halos equal to 28mm, 26mm and 37mm against the strains of E. coli, K. pneumoniae, and S. aureus respectively. As for the tests related to serial dilutions, we observed that after the 1/10 dilution, the extracts no longer had any inhibitory activity on the bacteria under study. However, these results demonstrate the potential of the soursop extract, especially the fruit, as a source of antibacterial compounds. However, it is worthwhile to continue more advanced research with Annona muricata.